White-water Rafting Tourism Potential at Bukit Baka Bukit Raya National Park Based on The Tourism Suitability Index - Slamet Rifanjani; Listiani, Kiara Ayu; Muflihati, Muflihati; Perdana, Doni Maja; Marwanto (Media Konservasi, 2024)
Bukit Baka Bukit Raya National Park (BBBRNP) is a national park that functions as a conservation area for flora and fauna of mountainous tropical rain forests as well as a water catchment area for two large rivers, namely the Melawi River (West Kalimantan) and the Katingan River (Central Kalimantan). This natural condition produces potential for BBBRNP as a tourism area, especially for white water rafting. One of the BBBRNP resorts that have the potential to become a tourism area is Belaban Resort, a white-water rafting spot. However, the existing possibility of white-water rafting has not been analyzed measurably. This research aims to determine the Tourism Sustainability Index (TSI) of white-water Rafting at Belaban Resort, BBBRNP. The study was conducted in March 2022. The method for determining the observation location used a purposive sampling technique. Data was analyzed using the Tourism Suitability Index (TSI) analysis. This research consists of ten observation points. The research results show that the suitability index for rafting tourism is included in the v(S1) with a suitability index value of 88.56%.